2019
DOI: 10.1021/acs.jpcc.9b02672
|View full text |Cite
|
Sign up to set email alerts
|

Transient Electron Spin Polarization Imaging of Heterogeneous Charge-Separation Geometries at Bulk-Heterojunction Interfaces in Organic Solar Cells

Abstract: Despite the importance of elucidating photoinduced chargegeneration mechanisms for the development of efficient organic solar cells (OSC), it has been quite difficult to characterize molecular geometries, electronic couplings, and charge mobilities in the initial photoinduced charge-separated (CS) states for the heterogeneous molecular environments in bulk-heterojunction interfaces between electron donor−acceptor domains in the photoactive layers. In this study, we employed a time-resolved electron paramagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 67 publications
(213 reference statements)
5
48
0
Order By: Relevance
“…1, when the triplet excitons are separated from each other to result in a negligible magnitude of exchange coupling (J z 0), spin correlations in the triplet-triplet pair may occur to induce diagonalized nine spin-states as the quantum superpositions of the singlet-triplet-quintet character through the spin-spin dipolar couplings of individual triplet species. This is quite similar to the spin-correlated radical pair (SCRP) model 33,34,[36][37][38][39][40][41][42] in the photoinduced long-range chargeseparation system generated by singlet or triplet precursors, causing the superpositions of the singlet-triplet characters when the J-coupling is small in the radical pairs. We herein demonstrate that the transportations of the SF-induced 5 (TT) and 1 (TT) characters can be distinguished on the T + T dissociation using the ESP of the correlated T-T state by applying TREPR spectroscopy to thin lms of 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-Pn).…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…1, when the triplet excitons are separated from each other to result in a negligible magnitude of exchange coupling (J z 0), spin correlations in the triplet-triplet pair may occur to induce diagonalized nine spin-states as the quantum superpositions of the singlet-triplet-quintet character through the spin-spin dipolar couplings of individual triplet species. This is quite similar to the spin-correlated radical pair (SCRP) model 33,34,[36][37][38][39][40][41][42] in the photoinduced long-range chargeseparation system generated by singlet or triplet precursors, causing the superpositions of the singlet-triplet characters when the J-coupling is small in the radical pairs. We herein demonstrate that the transportations of the SF-induced 5 (TT) and 1 (TT) characters can be distinguished on the T + T dissociation using the ESP of the correlated T-T state by applying TREPR spectroscopy to thin lms of 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-Pn).…”
Section: Introductionsupporting
confidence: 58%
“…This mechanism is also relevant to our recent low-temperature TREPR study for chargeseparation geometries (distance z 3 nm) in the bulkheterojunction interfaces of organic solar cells; it was concluded that the high-frequency in-plane stretching reorganization within aromatic polymer backbones promoted 1D charge-dissociation at the D:A domain interfaces. 41 The present SCTP spin polarization mechanism may thus pave new avenues to understand the nature of ultimate de-coupling and dissociation of two excitons for energy conversion. Although the coherent superposition of spin eigenstates was not directly detected, the present SCTP may be applicable to scalable quantum information processing via one-photon excitation because the sixteen possible EPR transitions from the nine sublevels ( Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations